Perceived stigma and discrimination is the cause for employees not to participate on the HIV/AIDS work programme. - Mthombeni, Dainnah Sonto (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MPhil (Industrial Psychology. Africa Centre for HIV/AIDS Management))--University of Stellenbosch, 2010.